Extinction for a p-Laplacian equation with gradient source and nonlinear boundary condition. Issue 15 (13th October 2022) - Xu, Xianghui; Cheng, Tingzhi
Abstract : We are concerned with extinction properties for a p -Laplacian equation with gradient source and absorption terms under nonlinear boundary condition. Based on the integral norm estimate method and the technique of differential inequalities, we establish some extinction results and the precise decay estimates of extinction solutions for this problem. Furthermore, we believe that the arguments used in this paper can also be applicable to the problem with nonlocal source instead of a gradient source.